Evaluation of Three Candidate Live-Attenuated Salmonella enterica Serovar Typhimurium Vaccines to Prevent Non-Typhoidal Salmonella Infection in an Infant Mouse Model - Khandra T. Sears; Shamima Nasrin; Scott M. Baliban; Danielle N. Council; Marcela F. Pasetti; Sharon M. Tennant (Vaccines, 2023)
Nontyphoidal Salmonella enterica (NTS) is a leading cause of foodborne illness worldwide, including in the United States, where infants show the highest incidence amongst all age groups. S. enterica serovar Typhimurium is one of the most frequently isolated serovars from NTS infections. We have developed several candidate live-attenuated S. Typhimurium vaccines to prevent NTS infection. The goal of the current study was to assess three live S. Typhimurium vaccine strains (CVD 1921, CVD 1921 ∆htrA and CVD 1926, which have two, three and four gene deletions, respectively) with various levels of reactogenicity and immunogenicity in infant BALB/c mice to predict how they would perform following peroral immunization of infants. We first tested intranasal immunization of 14-day-old mice with three doses delivered at 1-week intervals and evaluated antibody responses and protection against lethal infection with wild-type S. Typhimurium. The vaccines were administered to 14-day-old mice via the peroral route at 1- or 2-week intervals and to 28-day-old mice at 2-week intervals. The three vaccine strains were immunogenic following intranasal immunization of infant mice with vaccine efficacies of 80% (CVD 1921), 63% (CVD 1921 ∆htrA) and 31% (CVD 1926). In contrast, peroral immunization of 14-day-old mice yielded much poorer protection against lethal infection and only immunization of 28-day-old mice at 2-week intervals showed similar protective capacity as intranasal administration (CVD 1921: 83%, CVD 1921 ∆htrA: 43% and CVD 1926: 58%). CVD 1921 was consistently more protective than both CVD 1921 ∆htrA and CVD 1926, regardless of the route of vaccination, immunization schedule and age of mice. Anti-LPS serum IgG responses were similar between the three strains and did not correlate with protection. Due to previously observed reactogenicity of CVD 1921, CVD 1921 ∆htrA and CVD 1926 are our preferred vaccines, but these data show that further improvements would need to be made to achieve suitable protection in young infants when using peroral immunization.